2014
DOI: 10.1504/ijcg.2014.064726
|View full text |Cite
|
Sign up to set email alerts
|

Firm-level governance quality and dividend decisions: evidence from India

Abstract: Motivated by the outcome model of agency theory, the primary research issue addressed in this paper is to measure firm-level governance quality of Indian firms and examine its impact on dividend payment decision and payout-level decision. The companies with higher corporate governance quality have higher dividends payout ratios. It was found that board size, independence, monitoring quality, and managerial remuneration had positive impact on dividend payout. Insiders' (promoter directors) equity holding had a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…Gender diversity on boards not only brings in ethical values but also (Kramer and Konrad 2007) novel ideas to firms (Bernardi et al 2006), and compacts the influence of male directors, making board more answerable for their actions (Terjesen et al 2009). However, in the civil law environment, women executive directors have a strong benefit in supporting the management for their benefits on the cost of shareholders due to a weak monitoring mechanism (Prasanna 2014). Women executive directors could play a role in the reduction of dividend payment because they do not need it as a monitoring device (Prasanna 2014;Van Pelt 2013;Francis et al 2014).…”
Section: Women Directors On Boardsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gender diversity on boards not only brings in ethical values but also (Kramer and Konrad 2007) novel ideas to firms (Bernardi et al 2006), and compacts the influence of male directors, making board more answerable for their actions (Terjesen et al 2009). However, in the civil law environment, women executive directors have a strong benefit in supporting the management for their benefits on the cost of shareholders due to a weak monitoring mechanism (Prasanna 2014). Women executive directors could play a role in the reduction of dividend payment because they do not need it as a monitoring device (Prasanna 2014;Van Pelt 2013;Francis et al 2014).…”
Section: Women Directors On Boardsmentioning
confidence: 99%
“…However, in the civil law environment, women executive directors have a strong benefit in supporting the management for their benefits on the cost of shareholders due to a weak monitoring mechanism (Prasanna 2014). Women executive directors could play a role in the reduction of dividend payment because they do not need it as a monitoring device (Prasanna 2014;Van Pelt 2013;Francis et al 2014). Earlier studies (Hsu and Wu 2014;Cho and Kim 2007;Cheng and Courtenay 2006;Ruiz-Barbadillo et al 2007;Zhang 2008;Deshmukh et al 2010;Banerjee et al 2013) explain the negative effect of executive directors on dividend announcement because executive directors increase the supremacy of management on boards and support low-dividend payout decisions.…”
Section: Women Directors On Boardsmentioning
confidence: 99%
“…Independent directors can constrain opportunistic behaviours of managers regarding dividend policies, which often are prejudicial for shareholders and benefit managers. Thus, outside directors prefer to pay dividends instead of retaining earnings, because insider directors may mishandling cash retained within the company (Easterbrook, 1984;Wellalage et al, 2012;O'Connor, 2013;Prasanna, 2014).…”
Section: Independent Female Directors On Boardsmentioning
confidence: 99%
“…In this vein, dividend payout has been used by companies to reduce agency conflicts between managers and shareholders (Easterbrook, 1984;Jensen, 1986;La Porta et al, 2000). Therefore, in this context large stockholders face a less liquidity for their stocks and may, thus, increase dividend payout (La Porta et al, 2000;Prasanna, 2014 Previous literature demonstrates the negative effect of executive directors on BD on business failure (Hsu and Wu, 2014), financial disclosure (Cheng and Courtenay, 2006) and firm performance (Cho and Kim, 2007), among others. Furthermore, Ruíz- Barbadillo et al (2007) found that executive directors on BD increase management dominance over the board, and consequently these directors are less likely to support dividend payout, because these control mechanisms may monitor management actions.…”
Section: Executive Female Directors On Boardmentioning
confidence: 99%
See 1 more Smart Citation